Preparation of poly(3-hydroxybutyrate-co-hydroxyvalerate) films from halophilic archaea and their potential use in drug delivery - OGAN, AYŞE; MERTOĞLU, BÜLENT; ÇAKMAKÇI, EMRAH; BİRBİR, MERAL; DANIŞ, ÖZKAN (SPRINGER JAPAN KK, 2015)
Halophilic archaea offer a potential source for production of polyhydroxyalkanoates (PHAs). Hence, the experiments were carried out with five extremely halophilic archaeal isolates to determine the highest PHA-producing strain. PHA production of each isolates was separately examined in cheap carbon sources such as corn starch, sucrose, whey, apple, melon and tomato wastes. Corn starch was found to be a fairly effective substrate for PHA production. Among the strains studied here, the strain with the highest capability for PHA biosynthesis was found to be 1KYS1. Phylogenetic analysis based on 16S rRNA gene sequence comparison showed that 1KYS1 closely related to species of the genus Natrinema. The closest phylogenetic similarity was with the strain of Natrinema pallidum JCM 8980 (99 %). PHA content of 1KYS1 was about 53.14 % of the cell dry weight when starch was used as a carbon source. The formation of large and uniform PHA granules was confirmed by transmission electron microscopy and the biopolymer was identified as poly(3-hydroxybutyrate-co-hydroxyvalerate) (PHBV). PHBV produced by 1KYS1 was blended with low molar mass polyethylene glycol (PEG 300) to prepare biocompatible films for drug delivery. Rifampicin was used as a model drug and its release from PHBV films was investigated at pH 7.4, 37 A degrees C. It was found that PHBV films obtained from 1KYS1 were very effective for drug delivery. In conclusion, PHBV of 1KYS1 may have a potential usage in drug delivery applications.
Keywords: Halophilic archaea; poly(3-hydroxybutyrate-co-hydroxyvalerate); PHBV; Drug delivery; Rifampicin; RECOMBINANT ESCHERICHIA-COLI; HALOMONAS-BOLIVIENSIS LC1; BACTERIAL POLYHYDROXYALKANOATES; HALOFERAX-MEDITERRANEI; POLY(BETA-HYDROXYBUTYRATE) PRODUCTION; POLY(3-HYDROXYBUTYRIC ACID); MODERATE HALOPHILE; BIOSYNTHESIS; SPECTROSCOPY; HALOARCULA